Aramid Fiber Sheet Reinforcing Effects on the Local Damage in Concrete Plates Subjected to High Velocity Impact. Issue 3 (September 2013) - Beppu, Masuhiro; Kataoka, Shinnosuke; Takahashi, Jun; Krauthammer, Theodor
This study intended to evaluate the effectiveness of fiber sheet reinforcement on local damage mitigation in concrete plates subjected to high velocity impact. High velocity impact tests were conducted using concrete plates externally reinforced with aramid fiber sheets to examine the effects of the number of the fiber sheet laminates on the local damage. In a series of impact tests, strain time histories of the fiber sheet laminates were measured. Numerical simulations using the hydrocode ANSYS AUTODYN were carried out to reproduce the reinforcing effects by the fiber sheet laminates. Numerical results are discussed by comparing strain behavior and failure simulated numerically with test results. The reinforcing mechanism by the fiber sheets is discussed based on the numerical results.